Dislocated narratives in the alternative space-time of Christian Marclay’s The Clock - Ruiz Bañón, María Luz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Clock is a video installation in which the fictitious rhythm of celluloid is humanised through a narrative that operates from the anachronism of the appropriation of archive images. Marclay uses in his montage different mechanisms of narrative, sound and visual dislocation which, together with the anachronistic use of the filmic image, generate a heterochronous experience in the spectator. The result is the generation of an alternative to the concept of normalised space-time, which is re-signified as a multi-rhythmic and heterogeneous concept, offering the possibility of thinking another reality that gives us back the autonomy and control of its experimentation.